Cognitive poeticsas a translator`s perception instrument of time and space conceptsin - Gulmira K. Kazybek, Nurlan A. Askarov, Kulyash S. Ahmet, Kunimzhan S. Abdikalyk Altynay Sh. Askarova, Lyazzat M. Adilbe (Opción, 2019)
In article results of the linguistic experiment directed on revealing of features of perception and interpretation by translators of English- and Russian-speaking texts of an information-political orientation, are presented via different methods such as structural-functional analysis of texts. As a result, changes in the language of texts of an information-political orientation are shown that the modern political discourse is actually reduced to a set of propaganda advertising slogans. As a conclusion, every culture has its own national characteristics, without the knowledge of which the translator cannot fully express the emotional content of the text.